2021
DOI: 10.1101/2021.08.09.455664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEG spectral exponent as a synthetic index for the longitudinal assessment of stroke recovery

Abstract: Background: Quantitative EEG (qEEG) can capture changes in brain activity that follow a stroke. Accordingly, EEG metrics could be used to monitor patients state and recovery. Although qEEG metrics traditionally focus on oscillatory activity, recent findings highlight the importance of aperiodic (power-law) structure in characterizing pathological brain states. Objective: To assess neurophysiological impairment and recovery from mono-hemispheric stroke by means of the Spectral Exponent (SE), a metric that refle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The strong evidence that the aperiodic EEG component distinguishes states of wakefulness from sleep (Lendner et al ., 2020) and general anesthesia (Colombo et al ., 2019; Lendner et al ., 2020) motivated investigations of diagnostic value of this signal for unresponsive patients. In a clinical population, Lanzone et al (2022) proposed the aperiodic slope as an index for longitudinal recovery from stroke. To date, only a single study by Alnes et al (2021) assessed the spectral properties of pathologically unresponsive individuals and showed that the aperiodic component of the EEG is altered in patients in a coma, compared to healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…The strong evidence that the aperiodic EEG component distinguishes states of wakefulness from sleep (Lendner et al ., 2020) and general anesthesia (Colombo et al ., 2019; Lendner et al ., 2020) motivated investigations of diagnostic value of this signal for unresponsive patients. In a clinical population, Lanzone et al (2022) proposed the aperiodic slope as an index for longitudinal recovery from stroke. To date, only a single study by Alnes et al (2021) assessed the spectral properties of pathologically unresponsive individuals and showed that the aperiodic component of the EEG is altered in patients in a coma, compared to healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Aperiodic EEG measures are under investigation in patients. 8 Further, E/I imbalance has been demonstrated in the subacute phase after stroke in humans and transcranial stimulation at gamma frequency was able to reduce the degree of inhibition and improve performance in a motor task. 41,42 Alternatively, pharmacological agents to modify E/I ratio are available.…”
Section: Discussionmentioning
confidence: 98%
“…4–6 However, it was not until recently that the aperiodic, nonrhythmic component of neurophysiological signals gained more attention in animal and human data. 7,8 The aperiodic component defines the shape of PSD that typically shows exponentially decreasing power with increasing frequency and, accordingly, is largely dominated by a 1/f n -function. 7,9–12 The exponent n relates to the slope of the spectrum in log-log space.…”
mentioning
confidence: 99%
“…Electrophysiological observations in mice after stroke are not unlikely to occur in humans 39,40 . Spectral exponents in human stroke patients are under investigation 10 . A joint analysis of periodic and aperiodic parameters might enable future studies to further reveal their interference and prognostic value in stroke rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…delta-alpha ratio) [4][5][6][7][8] . However, it was not until recently that the aperiodic, non-rhythmic component of neurophysiological signals gained more attention in animal and human data 9,10 . The aperiodic component defines the shape of PSD that typically shows exponentially decreasing power with increasing frequency and, accordingly, is largely dominated by a 1/f n -function 9,[11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%